Landform classification for site evaluation and forest planning: integration between scientific approach and traditional concept - Azita Ahmad Zawawi,; Masami Shiba,; Noor Janatun Naim Jemali, (Universiti Kebangsaan Malaysia, 2014)
In this paper, we present an automated classification method of landform elements using an application of SAGA GIS software. The spatial assessment was done on the Yambaru forest area (YFA) in the northernmost part of Okinawa Island, Japan. This task is performed through the detailed elevation grid analyses from DTM of YFA with a spatial scale of 10 × 10 m2 supported by The Geospatial Information Authority of Japan. The classification has ten classes; high ridges, midslope ridges, upland drainage, upper slopes, open slopes, plains, valleys, local ridges, midslope drainage and streams. Classes were defined using the ‘topographical position index’ module and selected terrain variables were integrated to vegetation data for site evaluation. Information on terrain characteristics is very important to explain geographical constraints and map variability of natural resources in maintaining sustainable forest management as well as supporting decision making processes. Taking this into account, we adapted a traditional concept of forest terrain introduced by Sai On, a council member of the Ryukyu Kingdom (former name of Okinawa Island) when evaluating the potential site for forestry use.